Analisis Komunikasi Toxic dalam Perspektif Konseling Lintas Budaya pada Mahasiswa - Fina Nurhaliza; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Interpersonal communication is an important part of students’ social lives, especially in a multicultural campus environment. Differences in communication cultures often lead to misunderstandings, interpersonal conflicts, and the emergence of toxic communication behaviors when individuals lack adequate cultural sensitivity. This phenomenon was experienced by a student identified as A, who is from Dumai and struggled to adapt to the Minang communication culture due to a spontaneous speaking style that was perceived as rude by those around him. This study aims to analyze toxic communication from a cross-cultural counseling perspective among students and to identify counseling strategies used to assist the client’s social adjustment process. This study employs a qualitative approach using a case study design. Data collection techniques include observation, interviews, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions. The results indicate that interpersonal communication conflicts are influenced by differences in communication culture, low cultural sensitivity, poor emotional regulation, and the influence of the social environment. A cross-cultural counseling approach utilizing self-reflection, role-play, and empathy-building techniques helps clients enhance their cultural awareness, interpersonal communication skills, and emotional regulation. The findings of this study indicate that cross-cultural counseling is effective in helping students understand cultural differences in communication and build more harmonious social relationships in a multicultural environment.